Certified Kubernetes Administrator (CKA) - Van Vugt, Sander (Pearson IT Certification, 2020)
9+ Hours of Video Instruction Certified Kubernetes Administrator (CKA) Complete Video Course provides more than 9 hours of video instruction for IT professionals,Äìincluding IT Administrators, DevOps Engineers, Software Developers, IT Architects, and Hybrid Cloud Administrators,Äìpreparing to take the CKA exam, which requires an in-depth knowledge of how to develop, create, manage, store, and troubleshoot Kubernetes applications. The course includes labs, demonstrations, and lightboard explanations by Sander van Vugt, who has presented on dozens of Linux and Kubernetes courses. He introduces containers and Kubernetes, and moves through the process of creation, managing, and storing applications. He provides labs on setting up and managing clusters, and you'll also learn how to troubleshoot Kubernetes applications and cluster nodes. Sander shows how to manage deployments, services, ingress, and setting up storage, and walks through key troubleshooting scenarios. He ends the course with a sample exam for the user to practice before taking the real thing. Topics include: Module 1: Getting Started Module 2: Managing Pods and Deployments Module 3: Managing Kubernetes Clusters Module 4: Sample Exams About the Instructor Sander van Vugt has been teaching Linux classes since 1995 and has written more than 60 books about different Linux-related topics, including the best-selling RHCSA-RHCE 7 Cert Guide . Sander is also the author of more than 25 video courses, including Kubernetes Fundamentals . He teaches courses for customers around the world, and is also a regular speaker on major conferences related to open source software. Sander is also the founder of the Living Open Source Foundation, a non-profit organization that teaches open source to talent in different African countries. Skill Level Beginner/Intermediate Learn How To Best prepare to pass the Certified Kubernetes Application Developer (CKA) Exam Create a Kubernetes cluster Manage Pods and Deployments Manage Pod Storage and Networking Work with the API Manage scheduler settings Configure security Manage Kubernetes Networking Manage Cluster Nodes Troubleshoot Kubernetes Clusters and Applications Prepare for the CKA test Who Should Take This Course IT professionals that want to manage container deployment in their containerized devops environment using Kubernetes. Specifically: IT Administrators DevOps Engineers Software Developers IT Architects Hybrid Cloud Administrators Course Require...